Structures of the troponin core domain containing the cardiomyopathy-causing mutants studied by small-angle X-ray scattering - Matsuo, Tatsuhito (Biophys Physicobiol, 2015)
Troponin (Tn), consisting of three subunits, TnC, TnI, and TnT, is a protein in the thin filaments in muscle, and, together with another thin-filament protein tropomyosin (Tm), plays a major role in regulation of muscle contraction. Various mutations of Tn cause familial hypertrophic cardiomyopathy. These mutations are directly related to aberrations in this regulatory mechanism. Here we focus on the mutations E244D and K247R of TnT, which reside in the middle of the pathway of the Ca(2+)-binding signal from TnC to Tm. These mutations induce an increase in the maximum tension of cardiac muscle without changes in Ca(2+)-sensitivity. As a first step toward elucidating the molecular mechanism underlying this functional aberration, we carried out small-angle X-ray scattering experiments on the Tn core domain containing the wild type subunits and those containing the mutant TnT in the absence and presence of Ca(2+). Changes in the overall shape induced by the mutations were detected for the first time by the changes in the radius of gyration and the maximum dimension between the wild type and the mutants. Analysis of the scattering curves by model calculations shows that TnC adopts a dumbbell structure regardless of the mutations, and that the mutations change the distributions of the conformational ensembles so that the flexible N- and C-terminal regions of TnT become close to the center of the whole moelcule. This suggests, since these regions are related to the Tn-Tm interactions, that alteration of the Tn-Tm interactions induced by the mutations causes the functional aberration.